Chris Marker. Early Film Writings, edited by Steven Ungar. Translated by Sally Shafto, U of Minnesota P, 2024. - Jason C Grant (Studies in 20th & 21st Century Literature, 2026)
Review of Chris Marker. Early Film Writings, edited by Steven Ungar. Translated by Sally Shafto, U of Minnesota P, 2024. lxix + 199 pp.
Keywords: Chris Marker; filmmaking; criticism